Engineering of the Back Contact between PCBM and Metal Electrode for Planar Perovskite Solar Cells with Enhanced Efficiency and Stability. Issue 19 (27th June 2019) - Xiong, Shaobing; Yuan, Meng; Yang, Jianming; Song, Jingnan; Guo, Xuewen; Li, Xiang; Li, Bo; Liu, Xianjie; Duan, Chungang; Liu, Feng; Fahlman, Mats; Bao, Qinye
Abstract: The cathode interface plays a critical role in achieving high‐performance fullerene/perovskite planar solar cells. Herein, the simple molecule Isatin and its derivatives are introduced at the back contact [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM)/Al as a cathode modification interlayer. It is revealed that the Isatin interlayers facilitate electron transport/extraction and suppress electron recombination, attributed to the formation of negative dipole potential steps and the passivation of the interfacial trap density. The average power conversion efficiencies of the resulting devices are significantly improved by 11% from 17.68% to 19.74%, with an enhancement in all device parameters including short‐circuit current, open‐circuit voltage, and fill factor. The hysteresis index is found to disappear. In addition, such interlayer enhances device stability under ambient conditions compared to the control devices due to suppression of moisture‐induced degradation of the perovskite films. These findings provide a comprehensive understanding of the engineering of the back contact between PCBM and the metal electrode to improve efficiency and stability of perovskite solar cells. Abstract : Back contact between [6, 6]‐phenyl‐C61‐butyric acid methyl ester and metal electrode cathode in planar perovskite solar cell is modified via molecule Isatin, resulting in multiple beneficial effects, e.g., enhanced charge mobility, lower charge transfer resistance, higher charge conductivity, reduced energy barrier, and protective layer effect.